Age and sedimentary characteristics of beach sediments from Yongle Atoll, South China Sea: Implications for sediments supply in a coral reef system. (January 2020) - Li, Yali; Zou, Xinqing; Ge, Chendong; Tan, Ming; Tang, Meng; Liu, Xiaotong; Wang, Lisheng; Liu, Yang; Wang, Xiaohui
Graphical abstract: Highlights: The 230 Th ages of beach sediments of Yongle Atoll fall with a ca. 5000-yr time span. Tropical cyclone–generated waves and winnowing by tides are the main factors that influenced the grain size characteristics. The ages of coral clasts on a single island indicated that the coral sands provided within a relatively close time period. The atoll islands have different coral sediment supply rates. Abstract: Low-lying reef islands constructed from unconsolidated sediments are of growing interest due to concerns over the future stability of island landforms in response to climatic change and sea-level rise. Sediment characteristics, combined with the constituents and physical processes, are fundamental to understand the links between sediment production and their supply to an island's beach reservoir. The grain size, constituents, and 230 Th age of beach sediments from five islands at Yongle Atoll in the South China Sea were analyzed. Data reveal that coral grains are the dominant constituents of the beach sediments, followed by mollusks, coralline algae, foraminifera, Halimeda, and bryozoans. The mean grain sizes of the beach sediment were within a range of 226–4215 μm, and the coarsest sands were located near the passages in the atoll rim. Transportation by tropical cyclone–generated waves and winnowing by tides are potentially the main factors that influenced the grain-size characteristics. Calibrated 230 Th age dates for bulk sand samples date the beach sediment between 424 yr BP and 5953 yr BP. Dating of coral sand samples from the beach sediment provides ages of 686–5780 yr BP; the coral sands from a vertical section (1.2 m depth) located on the beach at Jinqing Island were dated at 1154–3824 yr BP. The age reversal on the vertical section, with similar ages of beach sediment on any single island and different age ranges on different islands in an atoll, indicates that the coral sediment supply processes occurred within a relatively close time period and that different islands had different sediment supply rates. The temporal link between the coral-dominated sediment production and the beach reservoir provides an important insight into understanding the sediments supply mechanism of atoll islands in the northwestern Pacific Ocean.